Contribution of leg muscle power and eye-foot coordination to football shooting results in PS UIR athletes - Yusup Agus Setiawan; Rices Jatra (Journal of Applied Movement and Sport Science, 2025)
Background Shooting is one of the fundamental techniques that determine success in football, serving as the primary key to scoring goals and winning matches. Shooting performance is influenced not only by technical skills but also by the player’s physical condition. Two physical components that are suspected to have a significant impact are leg muscle power and eye–foot coordination. Objectives This study aims to determine the extent of the contribution of leg muscle power and eye–foot coordination to shooting performance among PS UIR athletes. Methods The research employed a correlational method with a multiple correlation design. The population consisted of all PS UIR athletes, totaling 22 individuals, all of whom were included as the sample using a total sampling technique. The research instruments included the standing broad jump test to measure leg muscle power, an eye–foot coordination test, and a football shooting test. Results The results indicate that: (1) leg muscle power contributed 43.69% to shooting performance (r = 0.661 > r-table = 0.423), (2) eye–foot coordination contributed 32.83% (r = 0.573 > r-table = 0.423), and (3) the combined contribution of both variables reached 50.41% (r = 0.710 > r-table = 0.423). Conclusion It is concluded that leg muscle power and eye–foot coordination have a significant influence on shooting performance. These findings provide practical implications for coaches and athletes in designing more targeted and evidence-based training programs to improve shooting effectiveness during matches.